1997
DOI: 10.1038/ki.1997.73
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression for tyrosine hydroxylase in oxygen sensitive cells by hypoxia

Abstract: Carotid body type I cells and the O2 sensitive pheochromocytoma (PC12) cells release dopamine during hypoxia. Reduced O2 tension causes inhibition of an outward rectifying the O2-sensitive potassium (K) channel in the O2-sensitive pheochromocytoma (PC12) cell line, which leads to membrane depolarization and increased intracellular free Ca2+. We found that removal of Ca2+ from the extracellular milieu, inhibition of voltage-dependent Ca2+ channels, and chelation of intracellular Ca2+ prevents full activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 24 publications
2
68
0
1
Order By: Relevance
“…This is likely to be a complex process, given AP-1's apparent activation by oxidants (131) and anti-oxidants alike (143). Another signaling mechanism proposed is the hypoxia-induced modulation of intracellular Ca 2+ levels upstream of AP-1 activation (139,140,144,145). This increase is thought to activate AP-1 independently of HIF.…”
Section: Activating Protein-1 (Ap-1)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely to be a complex process, given AP-1's apparent activation by oxidants (131) and anti-oxidants alike (143). Another signaling mechanism proposed is the hypoxia-induced modulation of intracellular Ca 2+ levels upstream of AP-1 activation (139,140,144,145). This increase is thought to activate AP-1 independently of HIF.…”
Section: Activating Protein-1 (Ap-1)mentioning
confidence: 99%
“…AP-1 is involved in diverse cellular functions related to apoptosis, cell proliferation, cell differentiation, catecholamine biosynthesis, inflammation, xenobiotic metabolism, tumor invasion and angiogenesis (138). Genes regulated by AP-1 in hypoxia include tyrosine hydroxylase (139), VEGF (140), and endothelial NOS (eNOS) (131). AP-1 co-operates with other transcription factors such as HIF-1, GATA-2, NF-1 and NF-κB to complement the activation of hypoxia-sensitive genes (139)(140)(141)(142).…”
Section: Activating Protein-1 (Ap-1)mentioning
confidence: 99%
See 1 more Smart Citation
“…It may be significant that the 'TGGTTT' and G/C elements that mediate the response of Arabidopsis to hypoxia resemble the binding sites for the transcription factors activator protein-1 (Ap-1; TGATTC) and the Sp-1 family (GGGCCC), both of which contribute to the regulation of glycolytic enzyme genes by hypoxia. The Ap-1 proteins, c-Fos and c-Jun, are induced by hypoxia in neuronal cells, cancer cells and cardiac myocytes (Webster et al, 1993), and Ap-1 binding has been shown to be required for the induction of tyrosine hydroxylase as well as the endothelin-1 gene by HIF-1α (Hu et al, 1998;Millhorn et al, 1997;Yamashita, 2001). Both factors are present in most glycolytic enzyme gene promoters, often in multiple copies.…”
Section: Glycolytic Genes In Multicellular Eukaryotesmentioning
confidence: 99%
“…For example, an increase in [Ca 2ϩ ] i coupled to membrane depolarization has been associated with the activation of transcription factors (41,59). In addition, intracellular calcium has been demonstrated to regulate both CFTR (1) and ENaC (50) expression.…”
Section: Impact Of K ϩ Channel Activity On Enac and Cftr Expressionmentioning
confidence: 99%